Breynia disticha Snowbush: FPS73/FP073, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Snowbush (Breynia disticha), a rounded shrub known for its attractive variegated foliage. It details the plant’s characteristics, including its height, spread, leaf arrangement, and color. The Snowbush is suitable for various uses such as specimen planting, hedges, and indoor growth. It thrives in USDA hardiness zones 10 through 11 and requires full sun for dense growth. The document also covers the plant’s soil and light requirements, propagation methods, and pest resistance. Additionally, it highlights the Snowbush’s ornamental features and its potential as a landscape plant. Original publication date October 1999.